Analysis of Supplier Selection Using the Analytical Hierarchy Process Method (Case Study at PT. Seaport Services Indonesia) - Nurhayati, Nina; Handayani, Wiwik; Musnaini (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
Suppliers in the manufacturing industry have an important role because they determine product quality. The selection of suppliers is absolutely necessary so that the services produced have the quality according to the standards set by the company. If the quality of the supplier does not meet the criteria, it will cause several obstacles in the operational process. So this study aims to find out the best suppliers with priority criteria according to PT. Seaport Services Indonesia. The population in this study is a marine engine supplier owned by PT. Seaport Services Indonesia. The samples are 3 marine engine suppliers who provide sewage at PT. Seaport Services Indonesia. The sampling technique uses purposive sampling. The results of the analysis show that the best supplier for PT. Seaport Services Indonesia is Supplier B with the highest weight compared to the other two suppliers. As for the priority criteria is Flexibility.